1995
DOI: 10.1111/j.1464-410x.1995.tb00760.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistological findings in patients with superficial bladder carcinoma after intravesical instillation of keyhole limpet haemocyanin

Abstract: Immune-cell infiltration into the urothelium and enhanced activation (expression of class II antigens) suggests distinct processes of cellular antigen recognition, which could be detected for up to 9 months after the beginning of KLH therapy. This may represent a basic functional mechanism of KLH therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In fact, preimmunization with hemocyanins before tumor inoculation is essential to the success of the immunotherapy in humans [17,18] and mice [30]. Indeed, in patients with urinary bladder cancer under intravesical KLH therapy, a delayed-type hypersensitivity reactions (DTH) occurs [54]. This type of responses is mediated by Th1 lymphocytes secreting IFNγ, a response associated with the generation of cellular immunity [30].…”
Section: Discussionmentioning
confidence: 98%
“…In fact, preimmunization with hemocyanins before tumor inoculation is essential to the success of the immunotherapy in humans [17,18] and mice [30]. Indeed, in patients with urinary bladder cancer under intravesical KLH therapy, a delayed-type hypersensitivity reactions (DTH) occurs [54]. This type of responses is mediated by Th1 lymphocytes secreting IFNγ, a response associated with the generation of cellular immunity [30].…”
Section: Discussionmentioning
confidence: 98%
“…via presentation in MHC‐II), this molecule may also be present in MHC‐I. Consistent with this notion, immunohistological studies of biopsies from SBC patients undergoing immunotherapy with KLH showed a massive infiltration of mononuclear cells and CD4 + lymphocytes and, to a lesser extent, CD8 + lymphocytes and granulocytes [74]. These results can be interpreted, in part, in the context of a cross‐presentation of KLH [26], which has not been comprehensively studied.…”
Section: Discussionmentioning
confidence: 76%
“…Unexpectedly, we found that KLH and FLH induced an upregulation of MHC-I in BMDCs (Figure 3A), suggesting a role of cross-presentation in the processing of hemocyanins and consequential induction of CD8+ T cells related to the antitumor immune response (68). In this context, it is important to remark that immunohistological studies of biopsies from superficial bladder cancer patients who underwent immunotherapy with KLH showed a massive infiltration of mononuclear cells and CD4+ lymphocytes, as well as, to a lesser extent, CD8+ lymphocytes and granulocytes (69). In addition, during immunotherapy with KLH, a CD4+ lymphocyte response with an increase in CD8+ lymphocytes in the lymphatic nodules has been observed (70).…”
Section: Discussionmentioning
confidence: 99%